PROBLEM AND SOLUTION REGARDING WASTE IN THE PERSPECTIVE OF AL QUR’AN AND ITS IMPLEMENTATION IN SDG’S - Eny Winaryati; Eko Yulianto; Fitria Fatichatul Hidayah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Waste problem is steadily increasing by year. This waste problem is a problem on many levels, therefore, it needs participations from every elements of the society to work together insome sort of commitment based on a consensus and its implementation strategies. The problemof waste and its solution have been discussed in Al Qur’an, including the cause, the kind and place, the effects and the solution of the damage. Al Qur’an covers every aspects of life, even when it is not to be taken literally, because Al Qur’an was delivered in such poetic way it can be perceived in different ways that it will never be out of date till the end of time. Some verses discussing about waste and its solutions.  To realize those goals, on Millennium Summit of the United Nations (UN) in September2000, as much as 189 countries represented by their country heads or government heads signed a declaration titled as Millenium Development Goals (MDGs). There were 8 goals in this MDGs, with the seventh being to ensure the environmental sustainability.  As of September 25th 2015, UN has proclaimed and agreed to adopt the new global development agenda which was known as Sustainable Development Goals (SDGs). Agenda forSustainable Development” aims to push the environmental progress in sustainable development forward and to handle important issues such as pollutions, food waste, climate change, illegal trading of wild animals, and sustainable production and consumption. In SDGs, those goals werebased on the environment, starting from famine reduction to minimizing the gap in developing sustainable society around the world. It is important to have the participation from every relevant elements to reach those goals, especially the ones regarding environment.